Uit die geskiedenis van die ’’Corps Staatsartillerie" van die Zuid-Afrikaansche Republiek - Ploeger, Jan (Scientia Militaria - South African Journal of Military Studies, 2012)
The author of this article has put together diverse military historical notes on the "Corps Staatsartillerie" of the "Zuid Afrikaansche Republiek" and has dedicated his article to the memory of the late brig Willem Otto, in life Director of the Military Information Bureau.